COGNITIVE SOCIAL CAPITAL YANG MEMENGARUHI MOTIVASI DAN KEPUASAN KERJA KARYAWAN PADA RESTAURANT PIZZA HUT - Ghifary, Muhammad Tahajjudi; Esthi Putri, Ardiyanti (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Cognitive Social capital is an important component in human resource development. Companies must be able to encourage and facilitate existing human resources to maximize their performance. The purpose of this study was to examine the level of influence of cognitive social capital on motivation and job satisfaction of employees of Pizza Hut Ciliwung Branch, Malang City. This research is a quantitative study with a cross sectional approach and a sample of 32 respondents is the total population. This study succeeded in finding that there is a significant influence between cognitive social capital on motivation and job satisfaction of employees of Pizza Hut Ciliwung Branch, Malang City, either simultaneously or partially. This research is a unique research because it only looks at social capital from one dimension and is carried out at a food and beverage company that demands excellent customer service in order to maintain the quality of its business.